Kajian Teoritis Penerapan Self-Assessment untuk Meningkatkan Higher Order Thinking Skills (HOTS) - Adawiyah, Siti Rabiatul (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
The low ranking of Indonesia in the Programme for International Student Assessment (PISA) and Trends in International Mathematics and Science Study (TIMSS) in 2018 has led to the promotion of developing Higher Order Thinking Skills (HOTS) in education. The implementation of HOTS-oriented learning is expected to help Indonesia catch up in PISA rankings. The initial effort by the government involved using HOTS-type questions in the national exams of 2018. However, many education experts have criticized this approach, arguing that the learning process in schools has not yet been oriented towards HOTS. Implementing HOTS in the education system presents a significant challenge, especially when many aspects of learning still focus on factual knowledge and memorization. Therefore, there is a need to develop HOTS-oriented learning and integrate it into the educational process. One way to encourage HOTS in learning is by designing reflective learning through the application of self-assessment. This study aims to provide a theoretical review of the application of self-assessment to enhance HOTS. This research is a library research study. The author gathered data through literature review from various sources such as books, journals, academic papers, and other relevant documents and literature.